Princesas, Black Power e outros mares: a construção da identidade negra na produção infanto-juvenil de Kiusam de Oliveira - Lima, Emanuelle Valéria Gomes de (2021)
In view of the growing movement of the technological age, in which we find ourselves, especially, in a context marked by the various types of racisms, it is necessary to search for positive ethnic-racial representations that permeate the scope of literary language in Brazil, especially, after the implementation of federal law 10.639/03 and its respective Curricular Guidelines (2004). With this in mind, the present work proposes an analysis of Afro-Brazilian Identities constructions, based on the protagonists of Kiusam de Oliveira's children's production, composed by the works Omo-oba: histórias de princesas (2009), O mundo no black power de Tayó (2013) and O mar que banha a ilha de Goré (2014). Taking into account the trajectory of black characters in children's and youth literature and the legal frameworks instituted in Brazilian education after the enactment of Federal law 10.639 / 03, we question: in what aspects does Kiusam de Oliveira's literary production favor the reframing of black identities? To answer this question, we used bibliographic research covering racism and its impact on the literary trajectory, the stereotypes and the ideal beauty pattern raised by the literature, presenting counterpoints with the aforementioned productions. In this sense, the discussions take into account the perspectives of authors such as Cuti (2010), Maria Anória de J. Oliveira (2010), Regina Zilberman (2003), Nelly Novaes Coelho (2000), Leonardo Arroyo (1990), Edmir Perrotti (1986), Kabengele Munanga (1988), Édouard Glissant (2005), Frantz Fanon (2008), Homi K. Bahbha (2013), Neusa Santos Souza (1983), bell hooks (2019), Nilma Lino Gomes (2019), Patricia Hill Collins (2019), Grada Kilomba (2019), Reginaldo Prandi (2001), among others. Among the results achieved in this study, we realize that the narratives analyzed focus on the valorization of African cultures and deconstruct visions of the socially accepted body, thus elevating the ancestral heritage and female empowerment, through their main characters that not only subvert the literary order, but also social, since they list their subjective marks and recognize popular knowledge as a form of liberation. Thus, the characters make these narratives the driving force behind African history in Brazil, which, consequently, contributes to the affirmative constructions of their respective identities.